Pathways from irrigation to prosperity, nutrition and resilience: The case of smallholder irrigation in Mali - Nkonya, Ephraim M.; Magalhaes, Marilia; Kato, Edward; Diaby, Mahamadou; Kalifa, Traore (International Food Policy Research Institute, 2022)
Irrigation is increasingly promoted in Africa south of the Sahara, but the benefit streams of small-scale irrigation in Mali remain largely unknown. This study collected detailed quantitative data of irrigators and non-irrigators in two regions of Mali: Mopti, which is in the Sahelian zone, and Sikasso, the southernmost region of the country, which receives more rainfall. Econometric results show that the irrigation suitability, female household headship, proximity to markets and market participation increase the propensity to irrigate. The results suggest that small-scale irrigation investments have the potential to benefit women farmers directly. We used Two-Stage Weighted treatment effects multivariate regression to identify the impact of irrigation on selected outcomes. The impact assessment results show that crop income and diversification, market participation, employment, and dietary quality were substantially higher in irrigated farms compared to non-irrigated farms. Likewise, irrigating households had higher food security and higher dietary diversity. The results show that irrigation is a key entry point for combatting climate variability and change. However, the low adoption levels of improved water-lifting technologies are a major challenge. Limited promotion of solar and motorized pumps has contributed to the low adoption of these improved water-lifting technologies. A less profitable option, lifting water with a rope-and-bucket system, remains the most common water-lifting technology in the study areas. We find that investing in effective advisory services that target agricultural water management could increase uptake of more profitable irrigation technologies.